Risk Management Analysis on Twitch Application Use with Failure Mode Effect Analysis Method Based on Data Scraping and Interviews - Muhammad Firmansyah; Salman; Rahmat; Mastuty Ayu Ningtyas (Pasca Sarjana UKI, 2025)
This study examines risk management in the use of the Twitch application using the Failure Mode and Effect Analysis (FMEA) method based on scraping data. The main issue raised is the identification and evaluation of significant risks that can affect the operation and security of the Twitch application, including data security, user privacy, cyberattacks, and technical issues that can disrupt streaming services. The purpose of this study is to determine effective mitigation measures to reduce the impact of these risks. The method used is FMEA with assessment using a Risk Priority Number (RPN) to identify risks that require immediate attention and action. The results show that some risks have a high level of priority and require the implementation of strict security policies, the use of data encryption, two-factor authentication, and better infrastructure management. The conclusion of this study emphasizes the importance of effective risk management and the implementation of information security standards such as ISO 27001:2022 to improve the security and reliability of the system, as well as protect user data and privacy, so as to ensure a safe and smooth user experience in using the Twitch platform